PENGERTIAN, SEJARAH BERDIRI, DAN TUMBUH KEMBANG PESANTREN: STUDI KASUS DI PONDOK PESANTREN SURYALAYA TASIKMALAYA - Badriya Hisniati, Sally; Sariwati, Nova; Basri, Hasan; Suhartini, Andewi (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
This article aims to explain in detail the history of the establishment and growth of pesantren in the Indonesian archipelago, where there are concepts of salafiah pesantren and khalafiah pesantren. Salafiyah pesantren is a pesantren where a person seeks knowledge, by applying education that is guided by classical books or commonly known as yellow books. Khalafiyah pesantren or commonly known as modern pesantren is the result of the development of salafiyah pesantren, where education in this modern pesantren in addition to teaching religious knowledge is also taught general knowledge, with the aim of producing a generation that has skills in accordance with the times that exist today. The research method involved a literature review and analysis of current data related to the use of social media and its impact. The results of the study show that the Pesantren is transformative-active for its progress and is no longer a backward institution, the challenges of the times require the Pesantren to assimilate with the new culture. Now many Pesantren experience growth and development both in terms of curriculum, teaching and leadership patterns.